These tangled threads : a novel of Biltmore - Thomas, Sarah Loudin (Bethany House, a division of Baker Publishing Group, 2024)
"When a betrayal tears apart three young friends living in the shadow of Biltmore Estate, their friendship may be fractured forever. Years later, one of them risks exposure as a fraud unless she can mend the relationships and solicit help to create an original woven design for Cornelia Vanderbilt's 1924 wedding"--